Lentiviral vectors: design, biological properties, milestones and current major applications, hazards 1 - Naldini, Luigi (Henry Stewart Talks, 2014)
Properties of retroviral vectors: Genetic stability in target cells, Transgene expression, Fidelity of replication, Target cell spectrum, Transdution efficiency, Toxicity, RCR or WT virus contamination, Integration, Immunogenicity, Innate immune recognition of retroviral vectors, Lentiviral vectors, Nuclear import of viral genome, Challenges of developing lentiviral vectors, Viral vector design, Design of HIV-based vectors, Third generation lentiviral vectors, Lentiviral vector composition, Lentiviral gene transfer, Reducing HIV content of packaging system, Self-inactivating transfer vectors, HIV vector transcription in HIV-1 infected cells, Lentiviral vector biosafety, Lentiviral vectors: risk of insertional mutagenesis